Novel air-to-air data link system based on millimeter wave communication - Pengzheng XU; Qiyue YU; Hongchi LIN; Haining LIU (Tongxin xuebao)
In order to solve the problems of insufficient communication rate between networked fighters, signals being easily eavesdropped and interfered, and unsatisfactory networking performance in the existing air-to-air inter-aircraft data links, a millimeter wave communication air-to-air data link system was proposed.The millimeter wave communication technology was introduced into the data link system, and reconfigurable intelligent surface, orthogonal time frequency space modulation, integrated sensing and communication, and wireless ad hoc network technology were integrated.The analysis and simulation results show that the proposed system is superior to existing systems in terms of transmission bandwidth, anti-interception and anti-interference performance and hardware complexity and cost.At the same time, the proposed system faces technical challenges such as real-time beam tracking, which need further research to solve.